The Burgess Shale anomalocaridid Hurdia and its significance for early euarthropod evolution. - Daley, A; Budd, G; Caron, J; Edgecombe, G; Collins, D (2009)
As the largest predators of the Cambrian seas, the anomalocaridids had an important impact in structuring the first complex marine animal communities, but many aspects of anomalocaridid morphology, diversity, ecology, and affinity remain unclear owing to a paucity of specimens. Here we describe the anomalocaridid Hurdia, based on several hundred specimens from the Burgess Shale in Canada. Hurdia possesses a general body architecture similar to those of Anomalocaris and Laggania, including the presence of exceptionally well-preserved gills, but differs from those anomalocaridids by possessing a prominent anterior carapace structure. These features amplify and clarify the diversity of known anomalocaridid morphology and provide insight into the origins of important arthropod features, such as the head shield and respiratory exites.